Exílios, identidades e redes sociais : a dinâmica do conflito niceno-ariano na perspectiva de Hilário de Poitiers (343-361) - Vieira, Melissa Moreira Melo (2018)
In this dissertation, we aimed to analyze the political-religious conflict between nicenes and arians in the West in general, and in Gaul, in particular, during the years 343 and 361 AD. For this, we study the letters Ad Constantium Augustum and De Synodis, the invective Contra Constantium Imperatorem and the dossier Adversus Valentem et Ursacium, written by Hilary of Poitiers between 356 and 360. The works of the bishop of Poitiers represent a moment of important imperial interference in the political-religious configuration in the West during the government of Constantius, where, in the sociability complex, doctrinal discourses competed for legitimacy and imperial support. We seek to understand, through the works of Hilary of Poitiers and with a focus on the mapping of social networks between bishops mentioned in these, how these relations established within the episcopal coalitions reconfigured the western religious map, contributing to the resizing of power relations. To do so, we use the concept of representation of Roger Chartier, the concept of power of Pierre Bourdieu and Michel Foucault, identity of Tomaz Tadeu da Silva and social networks of Adam Schor as theoretical contributions. With regard to methodological tools, we use Laurence Bardin's Content Analysis